THE TECHNIQUES OF TRASNSLATION AND USES THE V DIAGRAM SYSTEM BY NEWMARK - Muji Endah Palupi (STIBA IEC JAKARTA, 2021)
The purpose of this research is to study about translation techniques and methods using the V-diagram system. Language is part of culture which plays an important role in social life. Language is used to express ideas orally or in writing. in grammar structure and vocabulary. Translation is an expression of a general term that refers to an idea from the source language (SL) to the target language (TL). Language translation is used to convey meanings and messages from different languages. In translation techniques, the theories studied are related to the processes and methods of language delivery. The purpose of translation is to reproduce different types of text. This research discusses translation techniques and methods. According to Peter Newmark, describes the translation techniques and methods using the V Diagram. This translation system is very simple and language conveyed is easy to understand by readers. Hopefully this research can be widely accepted so that readers will be interested in knowing more about the translation and its nuances